QAS Untuk Peningkatan Kualitas Pelayanan Bidang Administrasi Pada Kantor Desa Dengan Algoritma Cosine Similarity - Jumantri Tua Beruntung Silaen; Guidio Leonarde Ginting; Ryan Syahputra (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The development and use of computer technology is now increasingly sophisticated. Every year computer technology is growing with the passage of time. The use of computers is very important to obtain information in the registration process and data processing, as is the case at the Silaen Village Office. The Question Answering System and the Cosine Similarity method are computer-based systems to improve service quality with a question and answer system that aims to provide better alternatives. learn service material and make it easier to manage time in terms of administrative management so that it is easy to understand.